2016
DOI: 10.1038/srep23760
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Generation of Patterned Bubble Arrays on Printed Bi-functional Boiling Surfaces

Abstract: Bubble nucleation control, growth and departure dynamics is important in understanding boiling phenomena and enhancing nucleate boiling heat transfer performance. We report a novel bi-functional heterogeneous surface structure that is capable of tuning bubble nucleation, growth and departure dynamics. For the fabrication of the surface, hydrophobic polymer dot arrays are first printed on a substrate, followed by hydrophilic ZnO nanostructure deposition via microreactor-assisted nanomaterial deposition (MAND) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…However, because of the increased wettability, hydrophilic surfaces require larger superheat for nucleate boiling to occur and do not necessarily provide an enhanced heat transfer coefficient at low heat fluxes [3]. For further enhancements, several authors already suggested simultaneous implementation of hydrophobic and hydrophilic features on a single surface to produce a so called biphilic surface [3,6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the increased wettability, hydrophilic surfaces require larger superheat for nucleate boiling to occur and do not necessarily provide an enhanced heat transfer coefficient at low heat fluxes [3]. For further enhancements, several authors already suggested simultaneous implementation of hydrophobic and hydrophilic features on a single surface to produce a so called biphilic surface [3,6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…12 Various attempts were made in order to control nucleation of bubbles at the solid/liquid interface including the use of ultrasonic waves, 8 surface cavities, 9 temperature and surfactants, 1 and biphilic surfaces (chemically patterned hydrophobic/hydrophilic surfaces). 13 These attempts, however, require high pressures, the use of distinctive chemical moieties or temperature regulation. As many natural and synthetic surfaces are structured, 14,15 it is of high interest to use the potency of morphology for controlling heterogeneous nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side of the temperature spectrum a solid wall of a container accelerates the boiling of the liquid, but the adhered vapour bubbles block the heat transfer from the heated surface to the liquid. Release of the bubbles from the surface can be accelerated by coating the solid surface with hydrophobic and hydrophilic particles .…”
Section: Introductionmentioning
confidence: 99%